2009
DOI: 10.1007/s12192-008-0092-7
|View full text |Cite
|
Sign up to set email alerts
|

Low concentration of GA activates a preconditioning response in HepG2 cells during oxidative stress—roles of Hsp90 and vimentin

Abstract: Oxidative stress can be a significant cause of cell death and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Consistent with our finding, an in vitro study using HepG2 cells revealed that pre-treatment with low concentrations of H 2 O 2 (50 µM) induced increased levels of vimentin, and reduced the cleavage of vimentin following exposure to oxidative stress (26). It has been reported that the cleavage of vimentin by caspases results in the disruption of its filamentous structure, which may promote apoptosis by facilitating nuclear condensation and subsequent fragmentation and amplifying the cell death signal (26). Thus, fewer EPCs may undergo apoptosis induced by oxidative stress through the upregulation of vimentin.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our finding, an in vitro study using HepG2 cells revealed that pre-treatment with low concentrations of H 2 O 2 (50 µM) induced increased levels of vimentin, and reduced the cleavage of vimentin following exposure to oxidative stress (26). It has been reported that the cleavage of vimentin by caspases results in the disruption of its filamentous structure, which may promote apoptosis by facilitating nuclear condensation and subsequent fragmentation and amplifying the cell death signal (26). Thus, fewer EPCs may undergo apoptosis induced by oxidative stress through the upregulation of vimentin.…”
Section: Discussionsupporting
confidence: 91%
“…It is also responsible for subcellular localization of other organelles, especially nucleus and mitochondria [ 4 , 5 ]. One of the important functions of vimentin is to help the cells adapt to various kinds of stresses including heat [ 6 , 7 , 8 ], oxidative and electrophilic addition [ 9 ]. It is considered a marker of epithelial mesenchymal transition (EMT) and is highly expressed during cancer metastasis [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence, development, and treatment of cancer may also be related to cyclin B1. Deregulated expression of cyclin B1 may lead to a disrupted control of cell growth and a malignant phenotype (Egloff et al 2006 ; Chen et al 2009 ). Abundance of cyclin B1 (Porter et al 2000 ) and increased expression of cyclin B1 (Gomez et al 2007 ) are parallel to better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin B1 is a client protein of Hsp90 and also a key protein in the control of cell cycle transition from G2 to M phase (Ortiz et al 2002 ). Deregulated expression of cyclin B1 may induce a disrupted control of cell growth and a malignant phenotype (Egloff et al 2006 ; Chen et al 2009 ). Hence, the mechanism of the level change of cyclin B1 affected by hypoxia and 17-DMAG treatment in HCC cells was further explored in this paper.…”
Section: Introductionmentioning
confidence: 99%